Lizardfish fishery, biology and population dynamics of Saurida undosquamis (Richardson) off Visakhapatnam - Rajkumar, U; Sivakami, S; Rao, K Narayana; Kingsly, H Jose (Indian Journal of Fisheries, 2011)
The average annual estimated catch of lizardfishes off Visakhapatnam is 229 t, which formed 5.3% of the total landings during the period 1990-2001. Five species of lizardfishes are landed of which, Saurida undosquamis and S. tumbil are the dominant and contributed 88% to the total lizardfish landings of small trawlers. The fishery, biology and some aspects of population dynamics of S. undosquamis are studied. The estimated asymptotic length (L ) and growth constant (K) in S. undosquamis are 395 mm and 0.31 year –1 respectively. The fish attained maturity at 230 mm, with spawning period extending from October to March. The estimated mortality rates Z, F, and M in the species are 1.81, 1.05 and 0.76 respectively. The exploitation rate (E) of S.undosquamis is 0.58.